2021
DOI: 10.1007/s40596-021-01425-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Resident Support Following Patient Suicide: Assessing Resident Perceptions of a Longitudinal, Multimodal Patient Suicide Curriculum

Abstract: Objective Patient suicide is a common experience in psychiatry residency, and its effects on trainees can be profound. There are currently no ACGME Common Program Requirements for education about patient suicide, and a need exists for evidence-based curricula to prepare residents for this difficult outcome. Methods A comprehensive patient suicide curriculum was developed utilizing multiple modes of delivering content, including a training designed to foster built-in sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Gibbons et al, in a survey on 174 psychiatrists, found that, after a patient’s suicide, clinicians showed emotional and clinical distress [ 39 ]. Recently, McCutcheon et al, in a survey on 43 residents in psychiatry, underlined the necessity of improving clinicians’ coping strategies following a patient’s suicide [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gibbons et al, in a survey on 174 psychiatrists, found that, after a patient’s suicide, clinicians showed emotional and clinical distress [ 39 ]. Recently, McCutcheon et al, in a survey on 43 residents in psychiatry, underlined the necessity of improving clinicians’ coping strategies following a patient’s suicide [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the success of advertisements and educational content can also be predicted upfront by gauging the kind of feedback users are likely to have towards them [4]. Moreover, the analysis of multimodal data generated by patients can help predict their mental-states [30].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers focus on how to best support trainees through the painful and confusing reactions that follow a patient's suicide. McCutcheon and Hyman's brief report [12] describes the implementation and evaluation of a curriculum about the consequences to providers of a death by suicide, which covered both the emotional and the medico-legal implications. Agrawal et al [13] report their evaluation of a postvention protocol for residents who experience a patient's suicide.…”
mentioning
confidence: 99%